2021
DOI: 10.3390/antibiotics10111402
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Pattern of Resistance of Gram-Negative Bacteria Isolated from Blood Samples in Hospitalized Patients: A Single Center Retrospective Analysis from Southern Italy

Abstract: Background: Blood culturing remains the mainstream tool to inform an appropriate treatment in hospital-acquired bloodstream infections and to diagnose any bacteremia. Methods: A retrospective investigation on the prevalence of Gram-negative bacteria (GNB) and their resistance in hospitalized patients by age, sex, and units from blood cultures (BCs) was conducted from January 2018 to April 2020 at Sant’Elia hospital, Caltanissetta, southern Italy. We divided the patient age range into four equal intervals. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Overall, 64% of the tested isolates (57% from healthcare settings and 43% from swine) were resistant to three or more classes of antimicrobials and were thereby classified as MDR. MDR E. coli have been widely reported in livestock [15,38,39], food [40] and nosocomial infections [41][42][43][44][45]. As expected, the highest resistance rates to most of the substances, including AMP, SME, TRI, CIP, NAL and AZI, were found in isolates from hospital patients.…”
Section: Discussionsupporting
confidence: 62%
“…Overall, 64% of the tested isolates (57% from healthcare settings and 43% from swine) were resistant to three or more classes of antimicrobials and were thereby classified as MDR. MDR E. coli have been widely reported in livestock [15,38,39], food [40] and nosocomial infections [41][42][43][44][45]. As expected, the highest resistance rates to most of the substances, including AMP, SME, TRI, CIP, NAL and AZI, were found in isolates from hospital patients.…”
Section: Discussionsupporting
confidence: 62%
“…[28][29][30][31][32] While an Italian study showed that the most frequently isolated pathogens were K. pneumoniae (45.3%), followed by E. coli (15.4%). 33 This difference in primary bacteria might be associated with geographic area. As a study reported that K. pneumoniae was endemic in European countries bordering the Mediterranean Sea.…”
mentioning
confidence: 99%
“…Escherichia coli , Klebsiella spp, and Pseudomonas spp isolated in our bile samples are known as Multi Drug-Resistant (MDR) pathogens responsible for hospital bloodstream infection in the Mediterranean basin area [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%